2016
DOI: 10.5465/amj.2014.0506
|View full text |Cite
|
Sign up to set email alerts
|

Flourishing via Workplace Relationships: Moving Beyond Instrumental Support

Abstract: In a series of qualitative and quantitative studies, we developed a model of the functions of positive work relationships, with an explicit focus on the role that these relationships play in employee flourishing. Stories that employees told about positive relationships at work revealed that relationships serve a broad range of functions, including the traditionallystudied functions of task assistance, career advancement, and emotional support, as well as less studied functions of personal growth, friendship, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
265
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 290 publications
(283 citation statements)
references
References 67 publications
16
265
0
2
Order By: Relevance
“…This inevitably shapes women's preferences for particular career paths such as entrepreneurship. By acknowledging that both social interactions (Nanda & Sørensen, 2010) and organizations (Sørensen & Fassiotto, 2011) shape individual preferences for entrepreneurship, and integrating theories of gender inequality in career choices (Kossek et al, 2017) with evidence on the value of workplace relationships for career advancement (Colbert et al, 2016;McGinn & Milkman, 2013), we posit that startup founders can influence joiners' preferences for entrepreneurship. Drawing on social identification theory, we predict this influence to be more pronounced in same-gender matches and stronger for women based on (broadly defined) role modeling mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This inevitably shapes women's preferences for particular career paths such as entrepreneurship. By acknowledging that both social interactions (Nanda & Sørensen, 2010) and organizations (Sørensen & Fassiotto, 2011) shape individual preferences for entrepreneurship, and integrating theories of gender inequality in career choices (Kossek et al, 2017) with evidence on the value of workplace relationships for career advancement (Colbert et al, 2016;McGinn & Milkman, 2013), we posit that startup founders can influence joiners' preferences for entrepreneurship. Drawing on social identification theory, we predict this influence to be more pronounced in same-gender matches and stronger for women based on (broadly defined) role modeling mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Workplace relationships can offer mentoring, shape preferences and allow employees to flourish (Colbert et al, 2016), and also legitimize opportunities identified through experience, observation, and communication (Nanda & Sørensen, 2010;Pryor et al, 2016). Employees' satisfaction, performance, retention, and mobility are found to be molded by others at work, most often hierarchical superiors with more authority, seniority, and experience (Abraham, 2017;Artz et al, 2017;Artz & Taengnoi, 2016;Lazear et al, 2015;McGinn & Milkman, 2013), sometimes perceived as role models (Gibson, 2004).…”
Section: Individual Heterogeneous Preferences and The Value Of Mentmentioning
confidence: 99%
“…Despite those open questions, it is undeniable that individuals flourish in the workplace when they engage in trustworthy and positive relationships with co-workers (Colbert, Bono, & Purvanova, 2016). We could even say that individual uniqueness emerges from interactions with others (Gulati, Kilduff, Li, Shipilov, & Tsai, 2010).…”
Section: Philia or A Tale Of Trustmentioning
confidence: 99%
“…Ragins and Verbos [21] also indicated a positive relationship between low relationship quality (understood as the exploitation of one party by another) and dysfunctional behaviors.It is significant that researchers are more keen to examine the beneficial aspects of the quality of work relationships and the significance of this quality for organizational citizenship behavior (OCB), also in the field of sustainability (see, e.g., [9,22]). It is therefore no surprise that Colbert et al [23] indicate the need to describe the effects of negative relationships at work. In turn, Bowler and Brass [24] recommend expanding our knowledge on how these relationships influence counterproductive behavior.There is even sparser research on how CWB's relationship with QIRW is moderated by such key demographic features as employee sex, age, education, length of service and type of work.…”
mentioning
confidence: 99%
“…It is significant that researchers are more keen to examine the beneficial aspects of the quality of work relationships and the significance of this quality for organizational citizenship behavior (OCB), also in the field of sustainability (see, e.g., [9,22]). It is therefore no surprise that Colbert et al [23] indicate the need to describe the effects of negative relationships at work. In turn, Bowler and Brass [24] recommend expanding our knowledge on how these relationships influence counterproductive behavior.…”
mentioning
confidence: 99%